Love Affair in the Afternoon - Citra Rosalyn Anwar (Emik, 2019)
Korean drama is one of the most interesting shows for women in Indonesia nowadays. In spite of the fact that Korean drama offers many themes and genres, one of the most popular theme is love affair between married men (pebinor) and married women (pelakor). Even thpugh both are stigmatized, the former is not quite popular as compared to the latter, indicating that pelakor is more stigmatized than pebinor. In most of the dramas, the main actor is a married man, who has an affair with another woman. Using visual material of a selected Korean drama, entitled “Love Affair in the Afternoon” (2019) which deals with an extramarital relations between a married woman and a married man, this article analyses pieces of the scenes in the drama which include dialogues, monologues, locations and symbols in 16 episodes. The study shows that "Love Affair in the Afternoon" demonstrated the character of the main artist that is different from the common attributes attached to female lover (pelakor). As a wife, the portrait of Son Ji-eun's is associated with domestic roles and tends to be less demanding and expression which can be seen from her face, actions and speech. As a lover, Son Ji-eun is portrayed differently, she becomes more expressive in her attitude and action i.e. daring, and more opened. At the beginning she was totally obedient on her life and accepted everything until she finally decided to take a stance on her own destiny, and started realizing that she has an authority according to her own need. This Korean drama shows that lust or wealth is not always become a reason for someone to have an affair, there are many other reasons that make someone to have an extra marital relations. The drama shows that infidelity is not always dominated by men. It can be a man and a woman, but an affair is always considered negative. While mainstream media displays the common characters of female lovers as flirty, preening, and evil, this is not the case in this Korean drama. The drama still shows rejection of infidelity, suffering, separation, and divorce. This indicates that an affair is still something unacceptable. This drama has also succesfully reconstructed the image of the actor as a disturber and a socially hated person to become one who gets sympathy. It shows that media have the strong influenced in changing society’s point of view.